Management strategy in improving the performance of Legian Beach Hotel, Kuta in the new normal era - Gusti Kade Sutawa; Made Darsana (International Journal of Applied Finance and Business Studies, 2023)
After collapsing due to the Covid-19 pandemic, hotel management is trying to improve and develop strategies to improve the company's performance. This article aims to discuss the management strategy of the Legian Beach Hotel, Kuta in increasing performance after the Covid-19 pandemic. This paper is the result of qualitative research. Data collection was carried out through document studies, observations, and in-depth interviews with the hotel manager at Legian Beach Hotel, Kuta. The collected data were analyzed descriptively-qualitatively. The results of the study show that in improving the performance of Legian Beach Hotel, the management has carried out several strategies, namely: intensifying promotion and marketing, collaborating with stakeholders, implementing dynamic pricing, implementing human resource efficiency, and providing special services to hotel guests. In line with the rise of the Bali tourism market, the occupancy of Legian Beach Hotel has shown an increase from 15% during the Covid-19 pandemic in 2020 to 40% by the end of 2022.